Resolving the Rift between High Culture and Instinct: Bergenia ciliata - Begin, Marty (Homœopathic Links, 2017)
The case of a 34-year-old mother and naturopath progresses in a deeper way after applying Jan Scholten's plant system to arrive at Bergenia ciliata. The patient is able to integrate and solve her conflict between her intuitive and rational sides, which for her parallels her struggle to be herself in high mainstream society.
Keywords: Bergenia ciliata (elephant-eared saxifrage); Saxifragaceae; Saxifragales; Jan Scholten; Plant system; Intuitive; Rational; High culture; Instinct